Mothers' instinct : a novel of suspense - Abel, Barbara, 1969- (HarperVia, an imprint of HarperCollinsPublishers, 2023)
"A domestic suspense novel about next-door neighbors whose close friendship becomes something much more sinister after a tragic accident happens to one of their sons"--